2014
DOI: 10.4335/12.3.591-621(2014)
|View full text |Cite
|
Sign up to set email alerts
|

Dual Legitimacy in the Development of the Network City - A Case Study of Kaohsiung City Council

Abstract: This paper discusses the theoretical rheology of local governance from the bureaucratic system to the network city and explores whether and how such a city network can be developed in a dual local government system. This paper suggests that, in dual systems, councilors are nodes which extend their networks, and councilors together can construct a more comprehensive network than a city executive branch alone does, so as to remedy the executive branch’s deficiencies concerning city affairs. This paper chooses Ka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Based on the views of scholars and practitioners, strong citizen participation is typically regarded as an intermediate outcome that would be helpful for disaster relief and enhance the local emergency management capacity, especially when citizens' voluntary engagement is in line with the expectations of public officials (Kweit & Kweit, 2004;McEntire & Myers, 2004;Brudney & Gazley, 2009;McGee, 2011;Liao, Wu, & Li, 2014). Luna (2007) conducted a community-based emergency preparedness management research in the Philippines, and found that the built-in methods of citizen engagement in the emergency management process and energetic local volunteer organizations increased the likelihood of active participation from residents in emergency response tasks, which protected residents from potential risks.…”
Section: Citizen Participation In Local Emergency Managementmentioning
confidence: 99%
“…Based on the views of scholars and practitioners, strong citizen participation is typically regarded as an intermediate outcome that would be helpful for disaster relief and enhance the local emergency management capacity, especially when citizens' voluntary engagement is in line with the expectations of public officials (Kweit & Kweit, 2004;McEntire & Myers, 2004;Brudney & Gazley, 2009;McGee, 2011;Liao, Wu, & Li, 2014). Luna (2007) conducted a community-based emergency preparedness management research in the Philippines, and found that the built-in methods of citizen engagement in the emergency management process and energetic local volunteer organizations increased the likelihood of active participation from residents in emergency response tasks, which protected residents from potential risks.…”
Section: Citizen Participation In Local Emergency Managementmentioning
confidence: 99%